2022
DOI: 10.1056/nejmoa2117995
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 Vaccine against Critical Covid-19 in Adolescents

Abstract: Background The increasing incidence of pediatric hospitalizations associated with coronavirus disease 2019 (Covid-19) caused by the B.1.617.2 (delta) variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the United States has offered an opportunity to assess the real-world effectiveness of the BNT162b2 messenger RNA vaccine in adolescents between 12 and 18 years of age. Methods We used a case–control, test-negative design to assess vaccine effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
180
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 26 publications
4
180
2
1
Order By: Relevance
“…As of December 31, 2021, 54% of the population aged 12–17 years and 16% of those aged 5–11 years had completed a COVID-19 primary vaccination series. §§§§§ Increasing vaccination coverage among both age groups can reduce COVID-19–associated hospitalizations ( 6 ); enhanced outreach strategies are needed to address disparities in vaccination coverage by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…As of December 31, 2021, 54% of the population aged 12–17 years and 16% of those aged 5–11 years had completed a COVID-19 primary vaccination series. §§§§§ Increasing vaccination coverage among both age groups can reduce COVID-19–associated hospitalizations ( 6 ); enhanced outreach strategies are needed to address disparities in vaccination coverage by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Using a test-negative, case-control study design, vaccine performance was assessed by comparing the odds of having completed a 2-dose primary mRNA COVID-19 vaccination series during pregnancy among mothers of case-infants and control-infants (those with negative SARS-CoV-2 test results) (6). Participating infants were aged <6 months and admitted outside of their birth hospitalization to one of 20 pediatric hospitals during July 1, 2021-January 17, 2022 During this period, the SARS-CoV-2 Delta variant was the predominant variant in the United States through mid-December, after which Omicron became predominant.…”
mentioning
confidence: 99%
“…Effectiveness of maternal vaccination (i.e., vaccine effectiveness [VE]) against infant COVID-19 hospitalization was calculated using the equation VE = 100% × (1 – adjusted odds ratio of completing 2-doses of COVID-19 mRNA vaccines during pregnancy among mothers of case-infants and control-infants), determined from logistic regression models. Models were adjusted for infant age and sex, U.S. Census region, calendar time of admission, and race/ethnicity ( 6 ). Other factors were assessed (e.g., infant’s underlying health conditions, Social Vulnerability Index, and behavioral factors) but were not included in the final model because they did not change the odds ratio of vaccination by >5% or because data on many infants were not available (e.g., breastfeeding history, prematurity, or child care attendance).…”
mentioning
confidence: 99%
“… 8 In a study now reported in the Journal , Olson et al provide impressive evidence regarding the effect of the vaccine in hospitalized adolescents in the United States as part of the Overcoming Covid-19 surveillance network funded by the Centers for Disease Control and Prevention. 9 The investigators assessed data obtained at 31 selected hospitals in 23 states to determine the real-world effectiveness of the BNT162b2 vaccine against severe disease among adolescents between 12 and 18 years of age. A case–control, test-negative study design was used with two separate control groups, one in which hospitalized patients had negative results on testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (test-negative) and one in which patients had no symptoms of Covid-19 (syndrome-negative).…”
mentioning
confidence: 99%